Case Report: Successful ABO-Incompatible Deceased Donor Kidney Transplantation in an Infant Without Pre-transplant Immunological Treatment - Zhao, Daqiang; Zhu, Lan; Zhang, Shengyuan; Guo, Zhiliang; Wang, Lu; Pan, Tianhui; Sa, Rula; Chen, Zhishui; Jiang, Jipin; Chen, Gang (Frontiers in Medicine, 2022)
ABO blood group antibodies have not been generated or are at low titer during early infancy. Therefore, in theory, ABO-incompatible kidney transplantation (ABOi KT) may be successfully achieved in small infants without any pre-transplant treatment. We report here the first ABO-incompatible deceased donor kidney transplantation (ABOi DDKT) in an infant. The recipient infant was ABO blood group O, and the donor group A. The recipient was diagnosed with a Wilms tumor gene 1 (WT1) mutation and had received peritoneal dialysis for 4 months prior to transplant. At 7 months and 27 days of age, the infant underwent bilateral native nephrectomy and single-kidney transplantation from a 3-year-old brain-dead donor. No pre- or post-transplantation antibody removal treatment was performed, since the recipient’s anti-iso-hemagglutinin-A Ig-M/G antibody titers were both low (1:2) before transplantation and have remained at low levels or undetectable to date. At 11 months post-transplant, the recipient is at home, thriving, with normal development and graft function. This outcome suggests that ABOi DDKT without antibody removal preparatory treatment is feasible in small infants, providing a new option for kidney transplantation in this age range.